Association between gestational age and neonatal respiratory failure in term infants - Haotian Jiang; Xinghe Bu; Chao Chen; Jianguo Zhou (Scientific Reports)
Abstract The relationship between gestational age throughout the entire term period (37–41 weeks) and the occurrence of respiratory illness remains not fully understood. This population-based cohort study used birth data submitted by 50 states and the District of Columbia to the National Vital Statistics System database in USA to assess the association between gestational age and the incidence of neonatal respiratory failure (NRF) in term infants. Term singleton infants born from January 2021 to December 2022 were included in the analyses. The exposure variable of interest was the gestational age at birth. Primary outcome was NRF, defined by the need for assisted ventilation for over 6 h within the first days of life. Adjusted Odds ratios (aORs) compared NRF risk across gestational ages, with 39 weeks as the reference, adjusted for maternal and perinatal factors. In 4,978,703 term infants, NRF incidence at 37, 38, 39, 40, and 41 weeks was 1.7%, 0.9%, 0.6%, 0.7%, 0.8%, respectively. Compared to 39 weeks, the risk of NRF was higher at 37 weeks (aOR 2.08; 95% CI, 2.02–2.14), 38 weeks (aOR 1.27; 95% CI, 1.23–1.30), 40 weeks (aOR 1.18; 95% CI, 1.15–1.22), and 41 weeks (aOR 1.30; 95% CI, 1.25–1.35). Subgroup analyses confirmed similar trends across sex (male: aOR 2.07 at 37 weeks, 1.37 at 38 weeks, 1.12 at 40 weeks, 1.39 at 41 weeks; female: aOR 2.00 at 37 weeks, 1.34 at 38 weeks, 1.12 at 40 weeks, 1.40 at 41 weeks), delivery mode (vaginal delivery: aOR 1.96 at 37 weeks, 1.33 at 38 weeks, 1.10 at 40 weeks, 1.34 at 41 weeks; cesarean section: aOR 2.10 at 37 weeks, 1.37 at 38 weeks, 1.15 at 40 weeks, 1.48 at 41 weeks), and in infants born via elective cesarean section (aOR 2.51 at 37 weeks, 1.37 at 38 weeks, 1.09 at 40 weeks, 1.35 at 41 weeks). These findings highlight associations between gestational age within the term range and NRF risk, suggesting that careful consideration of delivery timing may be important for reducing respiratory complications in term infants.